Internalization Of Global Diversity Behavior Through Pancasila Project In Civic Education Learning - Nabilla Nadhar Aulia; Lita Yulia Anggraeni; Aurel Syarafina Ikhsani; Auliya Aenul Hayati; Rahmad Khodari (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
The article explores the concept of internalizing global diversity behavior through an activity that aims to improve students' Pancasila profile in learning Civic Education. By examining how Pancasila, the core concept of the Indonesian state, promotes tolerance and unity in variety and its significance. The author discusses how integrating a global perspective can enrich students' understanding of diversity and foster a sense of citizenship. With reference to relevant literature and the educational framework of the Merdeka Curriculum. Merdeka Curriculum is revolutionary regarding the field of education that aims to strengthen student independence in the learning process, increasingly emerging as a response to the need for more adaptive and contextualized education. Then, propose strategies to strengthen students' Pancasila profiles in order to effectively embrace global diversity. This study looks at how project-based learning might foster qualities of global diversity and strengthen the Pancasila Student Profile at SD Negeri Larangan 1 Cirebon City.  This research uses Mixed Method or commonly called Qualitative and Quantitative Methods, involving the principal, class teacher and 30 students who participated in the activities of the Pancasila Student Profile Strengthening Project. The data collection methods used are observation, questionnaires and interviews. This study found that the Pancasila Student Profile Strengthening Activity urges Global Diversity behavior with the results on the Pancasila Student Profile Strengthening Project variable in Civics Learning reaching 81% "Very Strong" and on the Global Diversity Behavior Internalization variable reaching 86% "Very Strong", understanding and honoring culture, reflecting on and interacting with other cultures, and taking responsibility related to diversity experiences, and social justice. Ideally, this study will be able to improve and implement global diversity behavior in everyday life, both in school and society.